Neuronal activity controls Bdnf expression via Polycomb de-repression and CREB/CBP/JMJD3 activation in mature neurons - Palomer, Ernest (2016)
It has been recently described that in embryonic stem cells, the expression of some important developmentally regulated genes is repressed, but poised for fast activation under the appropriate stimuli. In this work we show that Bdnf promoters are repressed by Polycomb Complex 2 in mature hippocampal neurons, and basal expression is guaranteed by the coexistence with activating histone marks. Neuronal stimulation triggered by N-methyl-D-aspartate application induces the transcription of these promoters by H3K27Me3 demethylation and H3K27Me3 phosphorylation at Serine 28 leading to displacement of EZH2, the catalytic subunit of Polycomb Repressor Complex 2. Our data show that the fast transient expression of Bdnf promoters II and VI after neuronal stimulation is dependent on acetylation of histone H3K27 by CREB-p/CBP. Thus, regulatory mechanisms established during development seem to remain after differentiation controlling genes induced by different stimuli, as would be the case of early memory genes in mature neurons.